The performance of Polylepis australis trees along their entire altitudinal range: Implications of climate change for their conservation - Marcora, Paula Inés (2008)
Altitudinal gradients are expected to heavily influence the general performance of mountain tree species. For this study we evaluated vitality, radial growth and reproductive efficiency in Polylepis australis (Rosaceae) throughout its complete altitudinal range in central Argentina. We selected seven forest fragments ranging from 900 to 2700 m a.s.l. In the field, we subjectively assigned vitality and seed productivity indexes to 12 P. australis trees per fragment. In addition, we cored and assessed for radial growth 10–18 trees per altitudinal level. In the laboratory, we individually weighed seeds from four or five trees from each altitudinal level and divided into two seed mass classes (light and heavy). We then tested for germination and monitored their seedlings for survival. Seedlings of three trees per altitudinal level were harvested after 40 days and assessed for dry mass. Seedlings of one to two trees per altitudinal level were monitored for survival until both leaves and roots had died. Our main results showed two types of responses to altitude: a unimodal relationship with an optimum at intermediate altitudes of around 1800 m a.s.l. for tree vitality, radial growth, seed productivity and seed mass; and an increase with altitude for in-vitro seed germination and seedling survival. A rise in temperature due to climate change could restrict P. australis to the upper most altitudes, where conservation of these forests will be a priority.